An Inconsistent Corrective Path: The Constitutional Court's Role as a Positive Legislator in Designing Indonesia's Simultaneous Elections - Hanif Alfattah; Lita Tyesta Addy Listya Wardhani (International Journal of Law, Crime and Justice, 2025)
This research examines the design of simultaneous elections in Indonesia as its main research object, a crucial discourse spurred by the persistent inefficiencies of a separated election model that produced divided governments. The discourse is marked by the shifting jurisprudence of the Constitutional Court (MK). The primary problem addressed is the Court’s jurisprudential inconsistency, which creates significant legal uncertainty for election organizers and political actors. Therefore, the objective of this research is to critically analyze the evolution of the Court's rulings on this matter and their impact on its shifting role into a positive legislator. This study employs a normative-juridical method, focusing on the doctrinal analysis of primary legal materials, particularly the series of relevant Constitutional Court rulings. The analysis reveals an inconsistent jurisprudential journey, starting from an activist stance that imposed a five-ballot simultaneous model through Ruling 14/PUU-XI/2013, with the aim of strengthening the presidential system. Then, in response to the systemic chaos and humanitarian costs of the 2019 election, the Court retreated to an "open legal policy" doctrine in Ruling 55/PUU-XVII/2019, exhibiting judicial self-restraint by deferring the choice of an alternative model to the legislature. Finally, it abandoned this position in a final interventionist decision, Decicion 135/PUU-XXII/2024, which stipulated a specific model separating national and regional elections. The main finding confirms that this latest ruling positions the MK as a positive legislator, significantly overstepping its traditional judicial authority. It is concluded that although the final ruling substantively produces a more rational election design, its inconsistent formation process has fundamentally undermined the principles of legal certainty and the balance of powers, thereby creating a problematic precedent for the future of Indonesia's constitutional governance.